Analysis Of Pollution Haven Hypothesis In World Trade Organization Member Countries - Kusuma, Gita Ayu; Setyari, Ni Putu Wiwin (Jurnal Ekonomi Kuantitatif Terapan, 2024)
The threat of climate change, justice and also inequality are subjective proxies in the Sustainable Development Goals (SDGs). Likewise with free trade carried out by every country in the world to meet the needs of society. Free trade began to appear when the rounds at the World Trade Organization (WTO) in Doha aimed to remove trade distortions in the international trade regime, so as to encourage an increase in world trade. The race of countries in the world to pursue wealth and prosperity has several impacts on the environment, one of which is global warming caused by greenhouse gases. The main greenhouse gas that continues to increase is carbon dioxide. The purpose of this study is to analyze the Pollution Haven Hypothesis (PHH) model in explaining the relationship between foreign investment, trade openness, income per capita, renewable energy consumption, non-renewable energy consumption and urban population on the environmental quality of WTO member countries. This research is an associative quantitative research conducted on WTO members with a sample size of 108 countries. Data collection was obtained through the World Bank Index which was then analyzed using the Autoregressive Distributed Lag (ARDL) method. The results of the study show that the Pollution Haven Hypothesis model not occurs in WTO member. However, in the long run the investment has a reduced emission impact on the host country. This is proof of the existence of the Halo Pollution Hypothesis.